Insights into islet development and biology through characterization of a human iPSC-derived endocrine pancreas model. Issue 3 (18th April 2016) - van de Bunt, Martijn; Lako, Majlinda; Barrett, Amy; Gloyn, Anna L.; Hansson, Mattias; McCarthy, Mark I.; Beer, Nicola L.; Honoré, Christian
ABSTRACT: Directed differentiation of stem cells offers a scalable solution to the need for human cell models recapitulating islet biology and T2D pathogenesis. We profiled mRNA expression at 6 stages of an induced pluripotent stem cell (iPSC) model of endocrine pancreas development from 2 donors, and characterized the distinct transcriptomic profiles associated with each stage. Established regulators of endodermal lineage commitment, such as SOX17 (log2 fold change [FC] compared to iPSCs = 14.2, p -value = 4.9 × 10 −5 ) and the pancreatic agenesis gene GATA6 (log2 FC = 12.1, p -value = 8.6 × 10 −5 ), showed transcriptional variation consistent with their known developmental roles. However, these analyses highlighted many other genes with stage-specific expression patterns, some of which may be novel drivers or markers of islet development. For example, the leptin receptor gene, LEPR, was most highly expressed in published data from in vivo -matured cells compared to our endocrine pancreas-like cells (log2 FC = 5.5, p -value = 2.0 × 10 −12 ), suggesting a role for the leptin pathway in the maturation process. Endocrine pancreas-like cells showed significant stage-selective expression of adult islet genes, including INS, ABCC8, and GLP1R, and enrichment of relevant GO-terms (e.g. "insulin secretion"; odds ratio = 4.2, p -value = 1.9 × 10 −3 ): however, principal component analysis indicated that in vitro -differentiated cells were more immature than adult islets. Integration of the stage-specific expression information with genetic data from T2D genome-wide association studies revealed that 46 of 82 T2D-associated loci harbor genes present in at least one developmental stage, facilitating refinement of potential effector transcripts. Together, these data show that expression profiling in an iPSC islet development model can further understanding of islet biology and T2D pathogenesis.